Beyond conventional transitional justice: Egypt's 2011 revolution and the absence of political will - Abou-El-Fadl, Reem (International journal of transitional justice, 2012)
After Egypt's January 2011 revolution ousted former President Hosni Mubarak, a conversation began amongst a number of international and Egyptian human rights groups regarding the need to promote international transitional justice precedents within the Egyptian context and to raise public awareness of them. This note argues that, in many ways, the Egyptian revolution surpassed the bounds of reformist transitional justice agendas. It begins by identifying two specific limitations in their scope: regarding the accountability of external actors and regarding the guarantee of economic and social rights. The article then describes the more far-reaching conceptions for change that were communicated in the key demands and subsequent campaigns of the 2011 revolution. Finally, it argues that Egypt's transition itself has stalled, as the ruling military council lacks the political will to propel transitional justice, rendering such discussions premature. It recommends that international practitioners take their cues from Egyptian actors negotiating these challenges, rather than proceeding without sufficiently questioning the context.